Intimate Partner Violence, Depression, and Anxiety Are Associated With Higher Perceived Stress Among Both Young Men and Women in Soweto and Durban, South Africa - Pakhomova, Tatiana E.; Dietrich, Janan Janine; Closson, Kalysha; Smit, Jenni; Hornschuh, Stefanie; Smith, Patricia; Beksinska, Mags; Ndung'u, Thumbi; Brockman, Mark; Gray, Glenda; Kaida, Angela (Frontiers in Reproductive Health, 2021)
OBJECTIVES Psychological stress is an important determinant of health, including for mental wellbeing and sexual health. However, little is known about the prevalence and psychosocial and sexual health correlates of perceived stress among young people in South Africa, where elevated life-stressors are an important driver of health inequities. This study examines the association between intimate partner violence (IPV), psychosocial and sexual health covariates and perceived stress, by gender, among South African adolescents and young adults. METHODS Using baseline survey data from AYAZAZI, a cohort study enrolling youth (16–24 years) from Durban and Soweto, we used the 10-item Perceived Stress Scale (PSS-10) to measure the degree to which an individual perceives their life situations as unpredictable, uncontrollable, and overloaded. Possible scores range between 0-40; higher scores indicating higher perceived stress. Crude and adjusted gender-stratified linear regression models examined associations between sexual health factors, experiences (young women) and perpetration (young men) of IPV, anxiety (APA), and depression (10-item CESD Scale, ≥10 = probable depression) and perceived stress. Multivariable models adjusted for age, income, sexual orientation, and financial dependents. RESULTS Of 425 AYAZAZI participants, 60% were young women. At baseline, 71.5% were students//learners and 77.2% earned ≤ ZAR1600 per month (~$100 USD). The PSS-10 had moderate reliability (α=0.70 for young women, 0.64 for young men). Young women reported significantly higher mean PSS scores than young men [18.3(6.3) vs. 16.4(6.0)]. In adjusted linear regression models, among young women experiences of IPV (β=4.33; 95% CI: 1.9, 6.8), probable depression (β=6.63; 95% CI: 5.2, 8.1), and symptoms of anxiety (β=5.2; 95% CI: 3.6, 6.8) were significantly associated with higher PSS scores. Among young men, ever perpetrating IPV (β=2.95; 95% CI: 0.3, 5.6), probable depression (β=6; 95% CI: 4.3, 7.6), and symptoms of anxiety (β=3.9; 95% CI: 2.1, 5.8) were significantly associated with higher perceived stress. CONCLUSION We found that probable depression, anxiety, perpetration of IPV among young men, and experiences of IPV among young women were associated with higher perceived stress. Critical efforts are needed to address the gendered stressors of young men and women and implement services to address mental health within violence prevention efforts.